Evaluasi Kebijakan Nilai Jual Objek Pajak (NJOP) Pajak Bumi Dan Bangunan (PBB P2) Dalam Meningkatkan Penerimaan Pendapatan Asli Daerah (PAD) Pada Badan Pendapatan Daerah (BAPENDA) Kota Bekasi Tahun 2019-2023 - Widuri, Neneng Ira; Nurmantu, Safri (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This Research aims to evaluate the policy, value, sale of objects, taxes land and building tax in increasing revenue, local revenue in Bekasi City regional revenue agencies in 2019-2023. The research method used by the researcher is a descriptive method with a qualitative approach. The data collection techniques used by the researcher are interview, observation and documentation with related details. The data analysis technique in this thesis is data triangulation, which means that this method uses several data sets, methods, theories, and/or researchers to answer a research question. Based on the results of this conclusion, the researcher concluded that, in the evaluation, the sales value policy for tax objects land and building tax in increasing revenue, local revenue in Bekasi City regional revenue agencies in 2019-2023 is still not effective, because the results of the realization of revenues over the five years are still below 100%. These balances can be analysed using the policy criteria model according to William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy.